Jenis-Jenis Jamur Rizosfer dan Jamur Busuk Batang Karet dari Perkebunan Karet (Hevea Brasiliensis Muell Arg.) di Desa Tajok Kayong - Mukarlina, Sisilia Hainawati Rahmawati, (Universitas Tanjungpura, 2019)
Rhizosphere is a fungus that plays an important role in the process of plant growth and development. This study aims to determine the morphological characters of rhizosphere fungi in rubber plants and rubber stem rot fungi. Sampling of rhizosphere fungi is carried out in rubber plantations. Tajok Kayong Village, Nanga Tayap District, Ketapang Regency. Isolation, identification was carried out at the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Tanjungpura University, from February to June 2018. method of isolation of rhizosphere fungi using dilution method and method of isolation of rubber stem rot fungi by dilution method and direct planting method.Â The isolation results showed 7 rhizosphere fungi isolates, namely members of Aspergillus sp. (JTS 5, 6, 7, 8), Mucor sp. (JTS 10), and members of the Penicillium sp. Species. (JTS 2, and Â JTS 9), and rubber stem rot fungi, namely members of the species Corticium sp.